Operando SAXS/WAXS on the a-P/C as the Anode for Na-Ion Batteries - Serena Margadonna (The Journal of Physical Chemistry C, 2018)
A complete chemical and morphological analysis of the evolution of battery electrode materials can be achieved combining different and complementary techniques. Operando small-angle X-ray scattering (SAXS) and wide-angle X-ray scattering (WAXS) were combined to investigate structural and electrochemical performances of an Na-ion battery, with amorphous red phosphorus in a carbon matrix (a-P/C) as the active anode material in a Swagelok-type cell. The charging process results in the formation of crystalline Na3P, while during discharging, the anode material returns to the initial a-P/C. From the analysis of the WAXS curves, the formation of crystalline phases appears only at the end of charging. However, SAXS data show that partial reorganization of the material during charging occurs at length scales nonaccessible with conventional X-ray diffraction, corresponding to a real space ordering distance of 4.6 nm. Furthermore, the analysis of the SAXS data shows that the electrode remains dense during charging, while it develops some porosity during the discharge phase. The presented results indicate that the combination of SAXS/WAXS adopted simultaneously, and nondestructively, on a working electrochemical cell can highlight new mechanisms of reactions otherwise undetected. This method can be applied for the study of any other solid electrode material for batteries.